(untitled) (International Journal of Language, Literacy and Translation, 2025)
It is important to produce graded readers (GRs) that appeal to language learners in order to encourage Extensive Reading (ER). Day and Bamford (1998) postulate that a good piece of text must be able to communicate with its readers. This is in line with Rosenblatt’s (1978) premise that the evocation in the reader, that is the experience of the reader with the text, is what marks successful communication, and is what positions the reader on the aesthetic stance during the reading encounter. This means successful learner material must be able to communicate with the second language (L2) reader with affect for the reader to enjoy the reading journey. Publishers often focus on the element of a good story to create an aesthetic reading experience. Whilst a good story or content is usually the main element in bringing about a text-reader transaction, “form” or the way content is expressed cannot be evicted from its role in evoking pleasure. Miall and Kuiken (2002), in their foregrounding theory, state that readers will be able to derive pleasure from their engagement with stylistic devices. Studies have shown that readers are able to respond to foregrounding regardless of their characteristics. Since GRs have the primary aim of bringing enjoyment to the language learner (Bassett, 2015), it is important to create texts that are capable of maximising the learners’ aesthetic response, and this includes taking into consideration the role of form. This paper, therefore, aims to highlight the importance of using stylistic devices in GRs.